Accurate Underwater Optical Wireless Communication Model With Both Line-of-Sight and Non-Line-of-Sight Channels - Chengwei Fang; Shuo Li; Ke Wang (IEEE Photonics Journal, 2022)
Underwater optical wireless communication (UOWC) systems have been widely studied to achieve high-speed wireless communications. To investigate and design UOWC systems, a mathematical model to characterize the accurate performance of UOWC systems is important. However, the previous mathematical models of UOWC systems have limitations, which mainly focused on the line-of-sight (LOS) link, and only considered the vertical incident background light or optical filters with constant transmittance for simplicity. To overcome these limitations, we establish an accurate UOWC system model, incorporating the previously overlooked impact of signal and sun lights incident angles and including both LOS and non-line-of-sight (NLOS) channels. Our proposed accurate UOWC system model is validated by Monte Carlo (MC) simulations. Results show that our proposed model can capture the changes of received powers of both signal and background lights with various transmitter and receiver alignments and orientations in both LOS and NLOS channels, which typically affect the signal-noise-ratio (SNR) and bit-error-rate (BER) performance of UOWC systems. Furthermore, we show that the incident angles of both signal and sun lights have significant impact on the system performance, and our proposed model can be used to optimize the PD rotation angle to improve the SNR performance. Therefore, the more accurate UOWC channel model established in this paper provides a fundamental framework for future UOWC system design and optimization.